Answer:
The given expression −12x+3−4x+5+32x simplifies to 8(2x + 1).
Explanation:
Consider the given expression −12x+3−4x+5+32x.
We need to simplify the above expression,
Give expression −12x+3−4x+5+32x
like terms are terms having same variables and powers.
Here, like terms are -12x, -4x, 32x and 3,5
We first write like terms together as,
⇒ (-12x - 4x + 32x)+ (3 + 5)
On simplifying, we get,
⇒ (-12 -4 +32)x + 8
⇒ (-16 +32)x + 8
⇒ (16)x + 8
Taking 8 common from both the terms , we get,
⇒ 8(2x + 1)
Thus, the given expression −12x+3−4x+5+32x simplifies to 8(2x + 1).